The lived experience following free functioning muscle transfer for management of pan-brachial plexus injury: reflections from a long-term follow-up study. Issue 11 (22nd May 2021) - Brito, Sara; White, Jennifer; Thomacos, Nikos; Hill, Bridget
Abstract: Background: Traumatic, pan-brachial plexus injuries result in major functional disability. Surgical advancements, such as free-functioning muscle transfers, are restoring physical capacity that was not achieved 3–4 decades ago. Despite reconstructive procedures, brachial plexus injury patients report chronic pain, changes in work circumstances, concerns about their appearance, increased reliance on others, and difficulty completing daily activities. This suggests that recovery needs to be considered to better deliver post-injury health services. Objectives: Investigate the lived-experience of patients following free-functioning muscle transfers for management of traumatic, pan-brachial plexus injuries. Better understand issues during recovery and implications for rehabilitation with this population. Methods: A phenomenological, qualitative design was employed that involved 5 participants who underwent surgery between 2007 and 2015. In-depth, semi-structured interviews were conducted and data were analyzed using interpretative phenomenological analysis. Results: Three interrelated themes were generated from the data. The first theme 'Experience of health care systems' captures the participants' reflections of their post-injury experience and health care received. The second 'Psychosocial considerations' consists of emotional responses, relationship disturbance, and coming to terms with the permanence of their changed arm. The last theme, 'Creating a new self-identity', relates to the participants experience of adjustment to their new circumstances. Conclusions: The findings of this study demonstrate that comprehensive medical coverage and access to expert brachial plexus injury health providers support patients following injury. However, recovery also requires the need for the patient to adjust and establish a new self-concept. Health care providers can assist patients by establishing positive therapeutic relationships, as well as, reducing the number of care providers by providing a continuity of care from the same health professionals. IMPLICATIONS FOR REHABILITATION: Individuals with pan-brachial plexus injuries felt it was beneficial to work with health care providers with extensive brachial plexus injury knowledge. Stable, long-term relationships with health providers during rehabilitation were reported as beneficial to recovery. Greater consideration of the process of adjustment and creating a new self-identity following pan-brachial plexus injury needs to be considered during rehabilitation.